Crystal Structures of Tcl1 Family Oncoproteins and Their Conserved Surface Features - John M. Petock; Ivan Y. Torshin; Yuan-Fang Wang; Garrett C. Du Bois; Carlo M. Croce; Robert W. Harrison; Irene T. Weber (The Scientific World Journal)
Members of the TCL1 family of oncogenes are abnormally expressed in mature T-cell leukemias and B-cell lymphomas. The proteins are involved in the coactivation of protein kinase B (Akt/PKB), a key intracellular kinase. The sequences and crystal structures of three Tcl1 proteins were analyzed in order to understand their interactions with Akt/PKB and the implications for lymphocyte malignancies. Tcl1 proteins are ~15 kD and share 25—80% amino acid sequence identity. The tertiary structures of mouse Tcl1, human Tcl1, and Mtcp1 are very similar. Analysis of the structures revealed conserved semi-planar surfaces that have characteristics of surfaces involved in protein-protein interactions. The Tcl1 proteins show differences in surface charge distribution and oligomeric state suggesting that they do not interact in the same way with Akt/PKB and other cellular protein(s).